Association between obesity and anemia in an nationally representative sample of United States adults: a cross-sectional study - Chen, Zhuo; Cao, Bingyan; Liu, Lu; Tang, Xudong; Xu, Hao (Frontiers in Nutrition, 2024)
Few studies are about the relationship between anemia and obesity, and previous studies have only paid attention to BMI; we first included body fat percentage (BF%) as an assessment indicator and divided it into quartiles, grouped participants into obesity and non-obesity used data from NHANES database. After adjustment for age, gender, ethnicity, education and family income, the level of soluble transferrin receptor (sTfR) and incidence of elevated CRP or HsCRP were progressively higher with increased BF%, whereas mean cell volume (MCV), natural logarithm (Ln) serum ferritin (SF) and Ln SF/sTfR were progressively reduced. Although a higher prevalence of anemia and lower hemoglobin was observed with increased BF%, but there was no statistical difference. Women in the highest BF% group demonstrated a significantly higher risk of iron deficiency compared to those in the lowest BF% group.